Second Selves, Second Stories : Unreliable Narration and the Circularity of Reading in Ford Madox Ford's "The Good Soldier" and Chuck Palahniuk's / David Fincher's "Fight Club" - Wald, Christina (My University, 2010)
The essay investigates how the The Good Soldier (1915) and Fight Club (1996), as well as the latter's film adaptation (1999), construct second selves of their autodiegetic narrators and thereby elicit second stories. In both novels, it is only toward the end of the narratives that readers realize the extent to which the narrator identifies with his close male friend who embodies his ideal of masculinity. With reference to the narratological concept of unreliability, the article explores how readers hence have to reassess their understanding of the narrated events and their value judgments. This belated recognition of the narrator's unreliability triggers a circular reading process, a structural device that selfconsciously comments on the hermeneutic circle and that is mirrored by circular concepts of biography and history in the content of both novels.
Keywords: 800